Prosocial Citizens Without a Moral Compass? Examining the Relationship Between Machiavellianism and Unethical Pro-Organizational Behavior - Castille, Christopher M. (Journal of business ethics, 2018)
Research in the organizational sciences has tended to portray prosocial behavior as an unqualified positive outcome that should be encouraged in organizations. However, only recently, have researchers begun to acknowledge prosocial behaviors that help maintain an organization’s positive image in ways that violate ethical norms (e.g., misrepresenting or exaggerating the truth, concealing damaging information about the firm). Recent scandals, including Volkswagen’s emissions scandal and Penn State’s child sex abuse scandal, point to the need for research on the individual factors and situational conditions that shape the emergence of these unethical pro-organizational behaviors (UPB). Drawing on trait activation theory, we argue that the “dark” trait of Machiavellianism should make individuals more willing to engage in UPB. Further, we argue that this willingness will be augmented when Machiavellians hold bottom-line-mentality climate perceptions (BLMCPs), or the perception that ethical standards matter less than organizational performance. Using data from 170 U.S. employees, results suggested that Machiavellians are more willing to engage in UPB, but that BLMCPs may not affect their motivation to engage in UPB. We discuss the study’s theoretical and practical implications, as well as avenues for research.